As the gradient on x=1 and x=2 are 4 and 5 respectively, therefore,
4 = 2a(1) + b
==> 2a + b = 4 ⋯⋯ (i)
5 = 2a(2) + b
==> 4a + b = 5 ⋯⋯ (ii)
Solving (i), (ii), we get,
a = 0.5, b = 3
As the curve also passes through origin, so c = 0.
Therefore, a = 0.5, b = 3, c = 0
This entry passed through the Full-Text RSS service — if this is your content and you're reading it on someone else's site, please read the FAQ at fivefilters.org/content-only/faq.php#publishers.
You are receiving this email because you subscribed to this feed at blogtrottr.com.